Pengaruh Game Edukasi Terhadap Keterampilan Berpikir Kritis Peserta Didik; Studi Kasus SDN Daleman I - Sukmawati; ST Wardatul Ainiyah; Eny Aulia Rohma (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study aims to analyze the effect of the use of educational games on critical thinkking skills of students at SDN Daleman 1. In the increasingly advanced digital era, educational games have become one of the interesting and interactive learning media. Educational games are believed to be able to encourage the development of critical thinking skills, such as analysis, synthesis, evaluation, and problem solving skills. These findings indicate that educational games can be an effective tool to improve students’ thinking skills, which are very important in facing the challenges of an increasingly complex world.